Other Respiratory Viruses Are Important Contributors to Adult Respiratory Hospitalizations and Mortality Even During Peak Weeks of the Influenza Season. (22nd September 2014) - Gilca, Rodica; Amini, Rachid; Douville-Fradet, Monique; Charest, Hugues; Dubuque, Josée; Boulianne, Nicole; Skowronski, Danuta M.; De Serres, Gaston
Abstract : This prospective study conducted during 2 influenza seasons shows that even during the peak weeks of influenza circulation, other respiratory viruses contribute substantially to adult respiratory hospitalizations and mortality and, among the elderly, may exceed influenza. Abstract : Background.  During peak weeks of seasonal influenza epidemics, severe respiratory infections without laboratory confirmation are typically attributed to influenza. Methods.  In this prospective study, specimens and demographic and clinical data were collected from adults admitted with respiratory symptoms to 4 hospitals during the 8–10 peak weeks of 2 influenza seasons. Specimens were systematically tested for influenza and 13 other respiratory viruses (ORVs) by using the Luminex RVP FAST assay. Results.  At least 1 respiratory virus was ide.jpegied in 46% (21% influenza, 25% noninfluenza; 2% coinfection) of the 286 enrolled patients in 2011–2012 and in 62% (46% influenza, 16% noninfluenza; 3% coinfection) of the 396 enrolled patients in 2012–2013. Among patients aged ≥75 years, twice as many ORVs (32%) as influenza viruses (14%) were detected in 2011–2012. During both seasons, the most frequently detected ORVs were enteroviruses/rhinoviruses (7%), respiratory syncytial virus (6%), human metapneumovirus (5%), coronaviruses (4%), and parainfluenza viruses (2%). Disease severity was similar for influenza and ORVs during both seasons. Conclusions.  Although ORV contribution relative to influenza varies by age and season, during the peak weeks of certain influenza seasons, ORVs may be a more frequent cause of elderly hospitalization than influenza.